Remote-sensing measurements and model simulations of peroxyacetyl nitrate (PAN) - Mahieu, Emmanuel; Clarisse, Lieven; Coheur, Pierre-Fraçois; Franco, Bruno; Notholt, Justus; Palm, Mathias; Strong, Kimberly; Wizenberg, Tyler (Zenodo, 2021)
Ground-based FTIR and IASI-A and -B measurements of PAN, supplemented with GEOS-Chem simulations. End users of these data sets are invited to contact the authors to make sure they are using the data properly and check about the possible availability of more recent products. : The University of Liège (ULiège) team has been primarily supported by the Fonds de la Recherche Scientifique (F.R.S. – FNRS, Brussels, Belgium; grant no. J.0147.18), and by the GAW-CH program of MeteoSwiss (Zürich, Switzerland). E. Mahieu is a Senior Research Associate with the F.R.S. – FNRS. His stay at the Lauder station, New Zealand, was supported by the F.R.S. – FNRS mobility grant n° 35143414. We thank the International Foundation High Altitude Research Stations Jungfraujoch and Gornergrat (HFSJG, Bern) for supporting the facilities needed to perform the FTIR observations at Jungfraujoch. The development of the IASI PAN product has been supported by the project OCTAVE (Oxygenated Compounds in the Tropical Atmosphere: Variability and Exchanges, http://octave.aeronomie.be) of the Belgian Research Action through Interdisciplinary Networks (BRAIN-be) research program (2017–2021; Research project BR/175/A2/OCTAVE) and by the IASI.Flow Prodex arrangement (ESA-BELSPO). L. Clarisse is Research Associate supported by the F. R. S.-FNRS. IASI is a joint mission of Eumetsat and the Centre National d'Etudes Spatiales (CNES, France). The IASI Level-1C data are distributed in near real time by Eumetsat through the EumetCast system distribution. The University of Bremen work has been supported by the German research foundation (DFG) in the project no. 268020496-TRR 172, within the Transregional Collaborative Research Center "ArctiC Amplification: Climate Relevant Atmospheric and SurfaCe Processes, and Feedback Mechanisms (AC)3" in subproject E02. The University of Bremen has further been funded by the German Ministry of Education and Research (BMBF) in the project TROSTRA (01LG1904A) and the by Senate of Bremen. We also thank the AWI Bremerhaven for logistical support at the AWIPEV station in Ny Ålesund and the personnel of the AWIPEV for their work. Eureka measurements were made at PEARL by the Canadian Network for the Detection of Atmospheric Change (CANDAC), primarily supported by the Natural Sciences and Engineering Research Council of Canada, the Canadian Space Agency, and Environment and Climate Change Canada (ECCC). We thank CANDAC/PEARL/PAHA PI James Drummond, Canadian Arctic ACE/OSIRIS Validation Campaign PI Kaley Walker, PEARL Site Manager Pierre Fogal, CANDAC Data Manager Yan Tsehtik, the CANDAC operators, and the staff at ECCC's Eureka Weather Station for their contributions to data acquisition, and for logistical and on-site support. : {"references": ["Mahieu et al (2021): First retrievals of peroxyacetyl nitrate (PAN) from ground-based FTIR solar spectra recorded at remote sites, comparison with model and satellite data"]}